Muscle structure governs joint function: linking natural variation in medial gastrocnemius structure with isokinetic plantar flexor function - Drazan, John F. (Biol Open, 2019)
Despite the robust findings linking plantar flexor muscle structure to gross function within athletes, the elderly and patients following Achilles tendon ruptures, the link between natural variation in plantar flexor structure and function in healthy adults is unclear. In this study, we determined the relationship between medial gastrocnemius structure and peak torque and total work about the ankle during maximal effort contractions. We measured resting fascicle length and pennation angle using ultrasound in healthy adults (N=12). Subjects performed maximal effort isometric and isokinetic contractions on a dynamometer. We found that longer fascicles were positively correlated with higher peak torque and total work (R(2)>0.41, P<0.013) across all isokinetic velocities, ranging from slow (30°/s) to fast (210°/s) contractions. Higher pennation angles were negatively correlated with peak torque and total work (R(2)>0.296, P<0.067). These correlations were not significant in isometric conditions. We further explored this relationship using a simple computational model to simulate isokinetic contractions. These simulations confirmed that longer fascicle lengths generate more joint torque and work throughout a greater range of motion. This study provides evidence that ankle function is strongly influenced by muscle structure in healthy adults.